Exact solutions of the nilpotent Dirac equation. (May 2020) - Rowlands, P; Rowlands, S
Abstract: Only a few exact solutions are known for quantum mechanical equations, and some of these tend to be complicated, requiring special mathematical techniques and multiple particular cases. The relativistic nilpotent Dirac equation has the virtue of allowing highly streamlined solutions for all the existing solvable problems and also adding others not solvable analytically by any other method.